Challenges and Opportunities in Measuring Sustainability: A View from Accounting Science (GESTIÓN Y TENDENCIAS, 2022)
Growing interest in sustainability has strongly driven investments that meet environmental, social, and corporate governance (ESG) criteria. In this article we show that the need for information allowing the sustainability of investments to be assessed and portfolios to be managed under ESG criteria has led to a proliferation of ESG indices controlled by various information providers that measure sustainability in different ways. Finally, we discuss the challenges and opportunities for accounting science and practitioners arising from this difficulty in measuring ESG factors.
Keywords: corporate governance; ESG; environmental responsibility